A sociology of bullying: Placing youth aggression in social context. Issue 4 (3rd February 2023) - Donoghue, Christopher; Pascoe, C.J.
Abstract: In this paper we review the sociological literature on peer aggression among adolescents and demonstrate how it can form the basis of a new subfield in sociology on the subject of bullying. Although sociologists have mostly avoided the term bullying in classic works on adolescent aggression, these studies suggest that institutional social control, status hierarchies and social inequalities provide important social context for youth aggression. While historically they have not been in dialog with each other, when taken together sociological research on youth status relations and social networks, systemic bias, school culture and social ecology can lay the foundation of a sociology of bullying. We suggest that if sociologists see this work as shedding light on issues of bullying, they can begin to play a larger role in the shaping of the national conversation on bullying and influence anti‐bullying programs in schools to take better account of the social dimensions of bullying.